The Students’ Perspectives on Observing Language Use in Social Media as Social Practice - Arina Isti'anah (Department of English Language Education, UIN Sunan Ampel Surabaya, 2017)
In this digital era, college students have become familiar with social media such as Facebook, twitter, and Instagram. For English Letters Students, they also use English when updating their status, tweeting their thought, or giving captions in their photos. That phenomenon results in the students’ interest in analyzing language use in social media, proven by some theses examining social media as the data. It means that the students have started to observe English language and literacy as social practice, for example is when a student observed English Letters students’ grammatical errors in their social media accounts. That fact reveals the student’s awareness of the importance of English language and literacy as social practice. A questionnaire was distributed to 64 students who take Language Research Methodology Class. Most of them access Instagram and Facebook in their daily life and spend half of their day accessing the media. Their activities involve reading posts on information and observe comments in the form of sentences. Pedagogical implication of the students’ responses was teachers should bring social issues which happen in society in which the students live to build their critical thinking. Therefore, the students are involved in social practice while developing their critical literacy.